A rare case of Takotsubo syndrome in a patient 5 months after heart transplantation. (18th December 2019) - Itzhaki Ben Zadok, Osnat; Ben‐Avraham, Ben; Hamdan, Ashraf; Tovar, Ana; Lyon, Alexander; Ben Gal, Tuvia
Abstract: Takotsubo syndrome is an acute heart failure syndrome with a pathogenesis that is attributed to sympathetic stimulation. This case report describes a unique case of a 5 month heart‐transplanted female patient who developed apical ballooning on an echocardiography exam performed following an emotional stress event. Detailed clinical investigations and imaging techniques confirmed the diagnosis of Takatsubo syndrome. Our case indicates that Takatsubo' s cardiomyopathy should be included in the differential diagnosis of heart‐transplanted patients presenting with sudden graft dysfunction mimicking acute graft rejection or acute coronary syndrome.